Engineering for Development as Borderland Activity. Issue 1 (2nd January 2020) - Robbins, Peter; Wield, David; Wilson, Gordon
ABSTRACT: The paper aims to build understanding of the recent growth of interest in engineering for international development as an emerging focus of new knowledge, practice, and community development. In the paper, we create a borderlands approach to studying the activities referred to as engineering for development and development engineering. These activities take place in 'borderland' spaces where new approaches are being tried out through creative engagement of networks and communities willing to integrate social as well as technical knowledge and practice. We analyze four cases, selected as exemplars of engineering for development, from a large data set of case studies to demonstrate the socio-economic impact of research. We found evidence of important and original engineering, which showed paradigmatic shifts in engineering knowledge and practice. There was ambivalence inside the engineering community about engineering quality, mixing pride in the building of new paradigms with modesty about whether new knowledge and practices were 'real' engineering. These findings provide evidence that engineering aimed at global development offers an exciting new 'borderlands' approach to engineering that warrants further study.